Community Based Diversity Management: Analysis of Community Activities Building Post-Conflict Social Harmony in Tual, Maluku Province, Indonesia - Yance Zadrak Rumahuru; Agustinus C. W. Gaspersz (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Ethnic and religious diversity have often been used as a source of conflict between different groups of people. However, pluralistic societies’ local wisdom offers a potential tool for long-term building of peace. This study investigated the practice of diversity management by post-conflict communities in Tual, Maluku Province, Indonesia, along with the factors that support community-based diversity management and forms of activities that contribute to the creation of social harmony in the city. Research was conducted in 2017 through a field study, using qualitative methods to observe the ways in which community groups in the region developed post-conflict social harmony, with data constantly updated to determine the dynamics of diversity management in the community. Two important findings were made. First, shared cultural and historical factors, availability of public spaces for encounters, and traumatic transformation influence and support diversity management and contribute to the creation of social harmony in Tual. And second, several communities were built by community initiatives as the foundation of managing diversity.Community daily activities proved to be effective in ensuring long-term peace building. Based on the reality of social lives in Tual, this study confirmed that a cultural approach is still relevant in efforts to end communal conflict and build social harmony, and synergy between stakeholders is needed to strengthen the social and cultural capital owned by community groups in conflict areas.